The Influence of Product Variation and Price on Consumer Satisfaction with Aice Ice Cream in Surabaya, East Java - Gideon, Mekhsa Caesar; Ferriswara, Dian; Arfani, Mochammad (International Journal of Education, Vocational and Social Science, 2025)
This study aims to analyze the influence of product variation and price on consumer satisfaction with Aice ice cream in Surabaya, East Java. Product variation and price are crucial factors in maintaining competitiveness in the highly competitive ice cream market. The research employed a quantitative approach with descriptive correlational analysis, using a questionnaire as the data collection instrument. The sample consisted of 96 Aice ice cream consumers selected through a simple random sampling technique. The analysis results indicate that product variation and price have a significant influence both simultaneously and partially on consumer satisfaction. The findings reveal that product variation and price positively and significantly affect consumer satisfaction simultaneously. Partially, product variation and price also have a positive and significant influence on consumer satisfaction. Based on these findings, it is recommended that Aice continue enhancing product variety to meet diverse consumer preferences and maintain competitive pricing to sustain consumer loyalty in the Surabaya market.